2020
DOI: 10.1097/mpg.0000000000002694
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis‐related Liver Disease is Associated With Increased Disease Burden and Endocrine Comorbidities

Abstract: Background: Cystic fibrosis-related liver disease (CFLD) is the leading nonpulmonary cause of mortality in cystic fibrosis (CF). We evaluated and compared the burden of disease and nonrespiratory comorbidities of those with severe CFLD and those without (noCFLD). Methods: A retrospective nationwide (Australia) longitudinal review (from 1998 to 2016) of severe CFLD patients compared with noCFLD controls (matched 1 : 1 for age, genotype, pancreatic insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…CFLD group had an increased prevalence of other CF comorbidities including respiratory failure, intestinal obstruction, rectal prolapse and constipation, diabetes, and lung transplantation. An Australian study by Singh et al 26 reported that patients with CFLD had increased disease burden requiring multiple hospitalizations for both respiratory and nonrespiratory indications, and were at increased risk for bone disease and diabetes. Thornton et al 8 showed that more than one‐third of patients with cirrhosis had ≥3 comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…CFLD group had an increased prevalence of other CF comorbidities including respiratory failure, intestinal obstruction, rectal prolapse and constipation, diabetes, and lung transplantation. An Australian study by Singh et al 26 reported that patients with CFLD had increased disease burden requiring multiple hospitalizations for both respiratory and nonrespiratory indications, and were at increased risk for bone disease and diabetes. Thornton et al 8 showed that more than one‐third of patients with cirrhosis had ≥3 comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…1 ), some directly related to liver dysfunction and some a consequence of liver dysfunction. People with severe CFLD are known to have endocrine comorbidities compared with matched people with CF without liver disease [33] .
Fig.
…”
Section: Cfld and General Endocrine Considerationsmentioning
confidence: 99%
“…Bone disease/osteoporosis: Osteoporosis is the predominant bone disorder seen in patients with CFLD. Those with CFLD have a 1.8 fold higher frequency of CF bone disease (CFBD) compared to matched controls with CF [33] . The increased risk of CFBD in those with liver disease is multifactorial and is associated with low BMI, IGF-1 deficiency, hypogonadism, vitamin D and vitamin K deficiencies.…”
Section: Cfld and General Endocrine Considerationsmentioning
confidence: 99%
“…Patients with CFLD, especially those with a severe phenotype, are at risk of significant malnutrition, micronutrient deficiencies and worse lung function [ 108 ]. The underlying causes are complex, including but not limited to poor intake associated with anorexia, delayed gastric emptying, and early satiety from abdominal distension (ascites, organomegaly); increased energy expenditure; and maldigestion/malabsorption [ 109 ].…”
Section: Cystic-fibrosis-related Liver Diseasementioning
confidence: 99%